A social innovation to empower community-led monitoring and mobilization for HIV prevention in rural Kenya: experimenting to reduce the HIV prevention policy-implementation gap - Goodman, Michael; Turan, Janet; Keiser, Philip; Seidel, Sarah; Raimer-Goodman, Lauren; Gitari, Stanley; Mukiri, Fridah; Brault, Marie; Patel, Premal (Frontiers in Public Health, 2023)
Introduction Strong policy guidance has recently emerged identifying focal points at multiple levels and across sectors to end the persistent HIV pandemic and related inequities. Reducing the policy-implementation gap, as with the evidence-policy gap, requires strategic alignment between interventional research and policy realms. Global- and national-level HIV policy indicate a need for community-led efforts to reduce HIV stigma, and increase uptake of HIV prevention tools. Methods This study assesses a process-driven approach to facilitating community-led efforts to reduce HIV stigma, and build a generative context for community-led HIV prevention. The study intervention combines an adapted group-based microfinance process, a novel psychological curriculum, and leadership development at a scale now involving over 10,000 rural Kenyans across 39 villages. Results Consistent with interventional goals, and current relevant psychosocial theories, we find collective emotion, and HIV stigma (blame and discrimination) significantly improve with more time participating in the in the program and novel curriculum. Further, HIV stigma predicts subsequent reporting of ever being tested for HIV, and the intervention led to the development of “HIV prevention resource committees” – groups of participants committed to undergo training to reduce HIV stigma and prevent HIV within their communities. Discussion Implications for further research to reduce the HIV policy-implementation gap are discussed, directly within this interventional context and more generally.